A prominent unified crosstalk model for linear and sub-threshold regions in mixed CNT bundle interconnects. (December 2021) - Kumar, Mekala Girish; Agrawal, Yash; Kumar, Vobulapuram Ramesh; Chandel, Rajeevan
Abstract: With the feasibility to scale the devices and interconnects in highly sophisticated VLSI technology, the demand for high-speed and low-power e -applications have also subsequently increased stupendously. Based on the applications and requirements, a VLSI system is operated in different modes as linear or sub-threshold. A unified analytical model for describing both these linear and sub-threshold modes is highly desirable. This has been innovatively presented in the current paper. Moreover, the futuristic and emerging mixed carbon nanotube bundle (MCB) as interconnects for both linear and sub-threshold region of operations has been considered. The essential signal integrity analysis comprising of several crosstalk effects such as associated transient response, delay and power have been analyzed. To evaluate this, analytical model is formulated and proposed using accurate unconditionally-stable finite-difference time-domain (USFDTD) technique. Utilizing the proposed model, it is investigated that linear mode of operation is good for realizing high-speed systems while sub-threshold is a preferable operation for applications targeted for low-power. Comprehensively, it is envisaged that the average power-delay-product in MCB interconnects operating in sub-threshold region is low and reduced by 74% compared to corresponding linear region of operation. Also, it is demonstrated that the proposed unified USFDTD based model for MCB interconnects operating in different modes of operation is stable and not constricted by the Courant condition. At maximum allowable time step, the proposed model is nearly 10 and 25 times faster than the conventional FDTD analytical and HSPICE simulation models, respectively. The results reveal that USFDTD technique provides better accuracy than the FDTD technique. The different performance analyses are performed at 22 nm technology node.